2020
DOI: 10.21577/0103-5053.20190160
|View full text |Cite
|
Sign up to set email alerts
|

An Acetal Acylation Methodology for Producing Diversity of Trihalomethyl- 1,3‑dielectrophiles and 1,2-Azole Derivatives

Abstract: 1 = n-decyl] were synthesized from respective alkyl methyl ketones or aldehyde via acetal acylation using trifluoroacetic anhydride and trichloroacetyl chloride. 1,1,1-Trihalo-4-methoxy-3-alken-2-ones with acid-compatible substituents were easily hydrolyzed to respective trihalomethyl-1,3-diketones. The 1,1,1-trihalo-4-methoxy-3-alken-2-ones and/or respective trihalomethyl-1,3-diketones were reacted regiospecifically with hydroxylamine hydrochloride, leading to isoxazole derivatives, and with hydrazines, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Bareño et al disclosed [3 + 2] cyclocondensation of trifluoromethyl-β-diketones 1 and hydroxylamine hydrochloride 55 to afford 5-hydroxy-5-trifluoromethyl-4,5-dihydroisoxazoles 237 regiospecifically (Scheme 75). [162] Pavlik et al reported the synthesis of 3-phenyl-5-(trifluoromethyl)isoxazole 239 by dehydration of 3-phenyl-5hydroxy-5-trifluoromethylisoxazoline 238, obtained by the cyclocondensation of 1,1,1-trifluoro-4-phenylbutane-2,4-dione 1 with hydroxylamine hydrochloride 55, using p-TsOH (Scheme 76). [163] Compound 238 in the 13 Aggarwal et al explored reaction of trifluoromethyl-βdiketones 1 with hydroxylamine 55 at variable pH (Scheme 77).…”
Section: Isoxazole Derivativesmentioning
confidence: 99%
“…Bareño et al disclosed [3 + 2] cyclocondensation of trifluoromethyl-β-diketones 1 and hydroxylamine hydrochloride 55 to afford 5-hydroxy-5-trifluoromethyl-4,5-dihydroisoxazoles 237 regiospecifically (Scheme 75). [162] Pavlik et al reported the synthesis of 3-phenyl-5-(trifluoromethyl)isoxazole 239 by dehydration of 3-phenyl-5hydroxy-5-trifluoromethylisoxazoline 238, obtained by the cyclocondensation of 1,1,1-trifluoro-4-phenylbutane-2,4-dione 1 with hydroxylamine hydrochloride 55, using p-TsOH (Scheme 76). [163] Compound 238 in the 13 Aggarwal et al explored reaction of trifluoromethyl-βdiketones 1 with hydroxylamine 55 at variable pH (Scheme 77).…”
Section: Isoxazole Derivativesmentioning
confidence: 99%